2009
DOI: 10.1021/np8006556
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Chemistry and Biology of New Generation Taxoids

Abstract: Among the numerous chemotherapeutic drugs, paclitaxel and docetaxel are among the most widely used against various types of cancer. However, these drugs cause undesirable side effects as well as drug resistance. Therefore, it is essential to develop “taxane” anticancer agents with better pharmacological properties and improved activity especially against drug-resistant cancers. Several laboratories have performed extensive SAR studies on paclitaxel. Our SAR studies have led to the development of numerous highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 59 publications
0
62
0
Order By: Relevance
“…To develop new taxane anticancer agents with fewer side effects, superior pharmacological properties, and improved activity against drugresistant human cancers, extensive structure-activity relationship studies on taxol and its congeners have been performed in different laboratories. Several novel second-and thirdgeneration taxoids with systematic modifications at the C2, C10, and C3'N positions were synthesized in Dr. Ojima's group (reviewed in Ojima & Das, 2009). It was determined that (i) the C3'-phenyl group was not an essential component for their potent activity and (ii) the modifications of the C10 position with certain acyl groups as well as the replacement of the phenyl group with an alkenyl or alkyl group at the C3' position made compounds 1-2 orders of magnitude more potent than the parent drugs (paclitaxel and docetaxel) against drug resistant human breast cancer cell lines.…”
Section: Csc-targeted Activities Of the New-generation Taxoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…To develop new taxane anticancer agents with fewer side effects, superior pharmacological properties, and improved activity against drugresistant human cancers, extensive structure-activity relationship studies on taxol and its congeners have been performed in different laboratories. Several novel second-and thirdgeneration taxoids with systematic modifications at the C2, C10, and C3'N positions were synthesized in Dr. Ojima's group (reviewed in Ojima & Das, 2009). It was determined that (i) the C3'-phenyl group was not an essential component for their potent activity and (ii) the modifications of the C10 position with certain acyl groups as well as the replacement of the phenyl group with an alkenyl or alkyl group at the C3' position made compounds 1-2 orders of magnitude more potent than the parent drugs (paclitaxel and docetaxel) against drug resistant human breast cancer cell lines.…”
Section: Csc-targeted Activities Of the New-generation Taxoidsmentioning
confidence: 99%
“…Furthermore, we found that introduction of a substituent (e.g., MeO, N 3 , Cl, F, etc.) to the meta position of the C2-benzoyl group of the second-generation taxoids, enhanced the activities 2-3 orders of magnitude higher than the parent drugs against different types of the drug-resistant cancer cells (Ojima & Das, 2009). The antitumor activity of SB-T-1214 (Figure 3), one of the leading candidates among the new generation taxoids studied in our laboratory, was assayed in vivo against a Pgp+ DLD-1 human colon tumor xenograft in SCID mice, as well as against highly drug-resistant CFPAC-1 pancreatic tumor xenografts.…”
Section: Csc-targeted Activities Of the New-generation Taxoidsmentioning
confidence: 99%
“…C-2-and C-3′-modified taxoids, etc. [4][5][6] Alcaide et al have utilized a variety of lactams as organic synthons for the construction of various alkaloid skeletons. 7,8 Mahajan et al have explored the lactam synthon approach towards the diastereoselective synthesis of functionalized octahydroisoquinolones, 9 pyrroloxazine, 10 tetra/octahydro-isoquinoline 11 and octahydroindole 12 ring systems.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey clearly reveals that lactams are important synthons for the synthesis of a variety of useful aza-heterocyclic systems. [4][5][6][7][8][9][10][11][12] Functionalized proline esters, the fivemembered azaheterocyclic systems, are important organocatalysts as well as having vital roles in biological systems. [13][14][15] The perhydroazirino [2,3-c]pyrrole family of natural products has been of interest to the scientific community since their isolation over 50 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Macrocyclic derivatives of diterpenoid paclitaxel exhibited cytotoxicity against pancreatic cell lines expressing multidrug-resistant genes. [15] In recent years, Cu I catalyzed azide-alkyne cycloaddition (CuAAC) received much attention as a method for construction of steroid/triterpenoid-based functional molecules. In view of the specific chemical properties of the formed by this method 1,4-disubstituted 1,2,3-triazoles (stable to metabolic degradation, capable of hydrogen bonding, favorable in the solubility and binding of bimolecular targets because of its relative planarity and strong dipole characteristics [16] ) triazole connecting macrocycles represent а challenging class of molecules with promising therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%